HUBUNGAN PENGETAHUAN, SIKAP, ASUPAN ENERGI DAN PROTEIN TERHADAP RISIKO KURANG ENERGI KRONIK (KEK) PADA WANITA USIA SUBUR DI DESA HIBUN KABUPATEN SANGGAU - Dwi Aprilianti; Jonni Syah R. Purba (Poltekkes Kemenkes Pontianak, 2018)
The importance of knowing the nutritional status of mothers before pregnancy can improve nutrition problems that will be sustainable in infants will be born. The risk of SEZ in women of childbearing age (WUS) has an impact on infants with LBW so that it will increase the number of malnutrition in Indonesia. This study aims to determine the relationship of knowledge, attitudes, energy and protein intake to the risk of chronic lack of energy (SEZ) in women of childbearing age (WUS) in Hibun Village, Sanggau District. This type of research is an observational study with a cross-sectional study design with a purposive sampling technique, the number of research samples is 70 respondents with criteria aged 18-35 years both those who have given birth and have not and are not pregnant. Data analysis included univariate and bivariate analysis using the chi-square test with a confidence level of 90% (Î± = 0.10). The results showed that there was a relationship between energy intake (p = 0.009) and SEZ risk in women of childbearing age and there was no relationship between knowledge (p = 0.196), attitudes (p = 0.226) and protein intake (p = 0.483) with SEZ risk in women of childbearing age in Hibun Village, Sanggau District. There is a relationship between energy intake and the risk of SEZ in women after fertility. There is no relationship between knowledge, attitudes and protein intake against the risk of SEZ in women after fertility. The need for counseling on SEZs for WUS to increase knowledge carried out at posyandu is carried out by health workers and cadres carried out periodically and continuously